PENGEMBANGAN MEDIA PEMBELAJARAN HANDOUT BERBASIS POTENSI LOKAL MATERI EKOSISTEM KELAS X SMAN 14 JENEPONTO - Suci Ramdayani; Ainul Uyuni Taufiq; Dahlia Patiung; Ummul Hasanah (Al-AHYA: Jurnal Pendidikan Biologi, 2021)
This study aims to develop handout learning media, determine the level of validity, practicality level, and the level of effectiveness of the media. By referring to the Research and Development (R&D) approach with a 4-D model, namely define, design, develop and disseminate. The product developed is in the form of handout learning media based on local potential ecosystem materials that are tested through validity, practicality and effectiveness tests. The research subjects are 10th grade students of SMAN 14 Jeneponto 2020/2021. The research instrument used was a teacher response questionnaire and a student response questionnaire to obtain practicality data, and test questions to obtain the level of effectiveness. The results showed that the handout learning media based on local potential of ecosystem materials had a validity level of 3.72 by material experts and design experts, then the practicality level was in the very positive category with an average value of 3.53. The level of effectiveness as a test of student learning outcomes is categorized as effective because it reaches 100%. so that the local potential-based Handout learning media is feasible to use because it meets the valid, practical and effective criteria.